2010
DOI: 10.1038/nrc2765
|View full text |Cite|
|
Sign up to set email alerts
|

Leukaemogenesis: more than mutant genes

Abstract: Acute leukemias are characterized by recurring chromosomal aberrations and gene mutations which are critical to disease pathogenesis. It is now evident that epigenetic modifications including DNA methylation and histone modifications contribute significantly to the leukemogenic phenotype. An additional layer of epigenetic complexity is the pathogenetic role of microRNAs in leukemias, and their key role in the transcriptional regulation of tumor suppressor genes and oncogenes. The genetic heterogeneity of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
231
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(235 citation statements)
references
References 188 publications
(214 reference statements)
3
231
0
1
Order By: Relevance
“…Although large-scale, global miRNA expression profiling assays have reported the correlation of signatures of many miRNAs with cytogenetic and molecular subtypes of acute leukemia, as well as patient response to treatment (16,(30)(31)(32)(33)(34)(35)(36)(37), the mechanisms underlying the deregulation of and the function of individual miRNAs in acute leukemia are largely unknown (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although large-scale, global miRNA expression profiling assays have reported the correlation of signatures of many miRNAs with cytogenetic and molecular subtypes of acute leukemia, as well as patient response to treatment (16,(30)(31)(32)(33)(34)(35)(36)(37), the mechanisms underlying the deregulation of and the function of individual miRNAs in acute leukemia are largely unknown (7).…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly accumulating evidence has revealed that miRNAs are strongly associated with cancer (3,(5)(6)(7). Recent studies suggest that a cluster of miRNAs, the miR-17-92 polycistron located at 13q31 [containing seven individual miRNAs including miR-17-5p (now named miR-17), miR-17-3p (now named miR-17*), miR-18a, miR-19a, miR-20a, miR-19b-1, and miR-92a-1], may function as an oncogene (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…30 Therefore miR-152 can be added to the growing list of so-called 'epi-miRNAs', such as miR-29b and miR-290, which control the regulation of DNMTs. 40 MiR-148 has recently been added to this list of epigenetic effector miRNAs because it targets DNMT3b. 41 As we have shown in this study, the degree of miR-152 methylation varies among t(4;11)-positive infant ALL samples and is highly predictive for clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…79 Others have added miR-290 to this list of so-called 'epi-miRNAs' upon the finding that miR-290 controlled DNA methylation and telomere recombination through retinoblastoma-like 2-dependent regulation of DNMTs. 80 Interestingly, a recent report demonstrated the discovery of a new class of miRNAs that directly (independent of target genes) mediated DNA methylation in plants. 81 After their loading into AGO4 clade proteins, these 24 nucleotide long miRNAs (lmiRNAs) directed DNA methylation at their own loci in cis as well as at their target genes in trans resulting a downregulation of target genes, likely via recruitment of de novo cytosine methyltransferase DRM2.…”
Section: Mirnas As Bystanders and Actors Of Epigeneticsmentioning
confidence: 99%